Bichectomy: technical systematization applied in 27 consecutive cases - Gustavo Steffen Alvarez; Evandro José Siqueira (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Despite buccal fat removal having been performed for a long time, its popularity has increased only in recent years, leading to a rise in the demand for bichectomy in plastic surgery clinics. Buccal fat pad removal is still considered controversial, even when properly indicated, especially with the lack of a systematized surgical technique to make it safe and reproducible. METHODS: The intraoral bichectomy described herein was systematically applied in 27 consecutive patients from January 5, 2016 to December 15, 2016. RESULTS: The mean patient age was 32 years; 15% were men, and 85% were women. Isolated buccal fat pad removal was performed in six patients (22%) and in combination with other procedures in 21 patients (78%). The main procedure combined was neck liposuction (55%), and most patients were operated under general anesthesia (93%). No permanent or significant complications occurred, and there were only two minor complications, i.e., inferior mandibular neuropathy and significant swelling, which improved without treatment during the following weeks. CONCLUSIONS: Buccal fat removal can be performed in a predictable, fast, and safe manner, leading to volumetric reduction of the lower third of the face, enhancing facial shape. When applied in a safe surgical environment, following all surgical security standards and considering the complex anatomical boundaries of the cheek, our technique can yield secure and satisfactory outcomes both for surgeons and patients.